HUTANG JANGKA PANJANG DAN PROFITABILITAS DI BANK SYARIAH: STUDI PADA PT BANK MUAMALAT INDONESIA - Yani, Dyah Fitri (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016, 2016)
Profitability is the company’s ability to generate profits by utilizing all available resources. The size of the profits for company affected by the increase of debt or bond. This study aim is to analyze the effect of longterm debt on profitability in PT Bank Muamalat Indonesia in the periode of 1999-2013. This study was analyzed using multiple linear regression model. Proxies used in the profitability ratio is return on equity (ROE) and disclosure of long-term debt is based on long-term debt to equity ratio (LDER) and long-term debt to asset ratio (LDAR). The results show that LDER has significant effect on profitability, when LDER increases the profitability of Bank Muamalat Indonesia is also rise, whereas LDAR has no significant effect on profitability of PT Bank Muamalat Indonesia.
Keywords: long term debt to equity ratio, long term debt to asset ratio, return on equity.